The Heat Death Line: Proposed Heat Index Alert Threshold for Preventing Heat-Related Fatalities in the Civilian Workforce. (August 2020) - Maung, Zaw; Tustin, Aaron W.
A threshold Heat Index (HI) can serve as the basis for advising the civilian workforce about the risk of heat-related illnesses. We conducted a systematic review and compiled reports of work-related fatalities from heat-related illnesses. We calculated the HI for each fatality. Our objective was to expand upon the military's concept of a "heat death line" and identify an HI alert threshold for the civilian workforce. We identified 14 publications totaling 570 heat-related deaths. In the meta-analysis, the median HI was 101 with a range of 62 to 137. Almost all deaths (96 percent and 99 percent of civilian and military fatalities, respectively) occurred when HI ≥80, which is our proposed heat death line. Some existing HI-based heat advisories are set at a higher temperature value. However, many occupational heat-related illnesses occur below these thresholds, resulting in low sensitivity and a false sense of security. In at-risk outdoor industries, HI ≥80 should trigger hazard awareness and protective actions.